Учатся ли политические партии? Оценка эффективности политической игры польских партий в процессе принятия избирательного закона в 2001 году - Кот, М. (Социология: теория, методы, маркетинг, 2005)
M.Kaminski in his article (2002) proposed a new way to measure effectiveness of activities of political parties aiming at electoral law changes, if we assume that their purpose was to maximize the number of seats in the parliament. The conclusion is that this effectiveness was very low in Poland during the first years of transformation. This article tries to answer the question: Do political parties successfully recognize which electoral law would give them more seats in the elections in 2001? This article proposes a new index measuring effectiveness of political actors, following which we find that this effectiveness was in 2001 higher, than in previous years, but still far from the maximal possible effectiveness. It still happens that actors choose an alternative less beneficial for them.